ANALISIS PERSEPSI MAHASISWA PGSD TERHADAP PENGGUNAAN ARTIFICIAL INTELLIGENCE DALAM PROSES PEMBELAJARAN - Adhinda Chaerani; Dhiva Meisa Aryenda; Zola Afifah; Jesi Alexander Alim; Mitha Dwi Anggriani (CV. Adiba Aisha Amira, 2025)
This study aims to analyze the perceptions of Primary School Teacher Education (PGSD) students regarding the use of Artificial Intelligence (AI), particularly ChatGPT, in learning. The research employed a quantitative approach using an online questionnaire distributed to students, followed by descriptive and simple inferential analysis. The findings indicate that the majority of respondents hold positive views toward AI, with 68% agreeing and 32% strongly agreeing that AI can enhance the quality of learning. Students perceived AI as beneficial in improving efficiency, material comprehension, creativity, and task completion. However, concerns were raised about potential negative impacts, such as a decline in critical thinking skills and independence due to overreliance on technology. Most respondents also emphasized the need for regulations and specific training to ensure the responsible and wise use of AI. The implications of this study highlight the crucial role of educational institutions in designing targeted AI integration policies, including training for both lecturers and students, as well as promoting AI as a supportive learning tool that fosters creativity and independence, rather than merely serving as an instant problem-solving instrument. This study recommends a wise and responsible integration of AI in higher education.